Misconceptions and biases in German students' perception of multiple energy sources: implications for science education. Issue 6 (12th April 2016) - Lee, Roh Pin
ABSTRACT: Misconceptions and biases in energy perception could influence people's support for developments integral to the success of restructuring a nation's energy system. Science education, in equipping young adults with the cognitive skills and knowledge necessary to navigate in the confusing energy environment, could play a key role in paving the way for informed decision-making. This study examined German students' knowledge of the contribution of diverse energy sources to their nation's energy mix as well as their affective energy responses so as to identify implications for science education. Specifically, the study investigated whether and to what extent students hold mistaken beliefs about the role of multiple energy sources in their nation's energy mix, and assessed how misconceptions could act as self-generated reference points to underpin support/resistance of proposed developments. An in-depth analysis of spontaneous affective associations with five key energy sources also enabled the identification of underlying concerns driving people's energy responses and facilitated an examination of how affective perception, in acting as a heuristic, could lead to biases in energy judgment and decision-making. Finally, subgroup analysis differentiated by education and gender supported insights into a 'two culture' effect on energy perception and the challenge it poses to science education.